PMU emulation for static security analysis of power system - Shukla D.; Singh S.P. (My University, 2025)
This paper attempts to emulate Phasor Measurement Unit (PMU) for Static Security Analysis of power systems, PMU's are enablers for real time and near real-time analysis of the power system. They are being integrated into the power system for enabling enhanced monitoring and control of the network. A methodology is presented for emulation of PMU and storage layout of data obtained from the emulation. A technique enabling the emulation of the PMU's specifically for Static Security Analysis will be of great use for analysis of the system by the researchers and scientists working in the power sector. Newton-Raphson will be used for solving the non-linear power flow equations while emulating the PMU in this paper. Emulation of IEEE 14 bus test systems has been demonstrated using the proposed method in MATLAB and the results obtained are presented in the paper. © 2016 IEEE.